2017
DOI: 10.1017/eaa.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

What is ‘European Archaeology’? What Should it be?

Abstract: ‘European archaeology’ is an ambiguous and contested rubric. Rooted in the political histories of European archaeology, it potentially unites an academic field and provides a basis for international collaboration and inclusion, but also creates essentialized identities and exclusionary discourses. This discussion article presents a range of views on what European archaeology is, where it comes from, and what it could be.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The current dominant standpoint of archaeologists with regards to Europe can be found in the first pages of a recent article by Babić et al (2017) 6 and can be summarized in two words: stay out. While some of its contributors express more nuanced positions, Robb and Babić explicitly discourage interaction in the opening section of the article by stating that ‘to try to build an emotive commitment to European identity [using archaeology] is a bad idea’ (Babić et al, 2017: 6). The two authors argue instead for ‘an organizational, not emotive, normality for “European archaeology”’ (Babić et al, 2017: 7).…”
Section: The Response Of European Archaeologymentioning
confidence: 99%
See 2 more Smart Citations
“…The current dominant standpoint of archaeologists with regards to Europe can be found in the first pages of a recent article by Babić et al (2017) 6 and can be summarized in two words: stay out. While some of its contributors express more nuanced positions, Robb and Babić explicitly discourage interaction in the opening section of the article by stating that ‘to try to build an emotive commitment to European identity [using archaeology] is a bad idea’ (Babić et al, 2017: 6). The two authors argue instead for ‘an organizational, not emotive, normality for “European archaeology”’ (Babić et al, 2017: 7).…”
Section: The Response Of European Archaeologymentioning
confidence: 99%
“…While some of its contributors express more nuanced positions, Robb and Babić explicitly discourage interaction in the opening section of the article by stating that ‘to try to build an emotive commitment to European identity [using archaeology] is a bad idea’ (Babić et al, 2017: 6). The two authors argue instead for ‘an organizational, not emotive, normality for “European archaeology”’ (Babić et al, 2017: 7). In practice this entails a complete separation from the developments taking place in Europe and goes against the realization of European officials that an emotive commitment to the European Union is imperative for its survival (Tusk, 2018).…”
Section: The Response Of European Archaeologymentioning
confidence: 99%
See 1 more Smart Citation
“…As argued by Cris Shore and Susan Wright, cultural policies do ‘not only impose conditions, as if from “outside” or “above”, but influence people’s indigenous norms of conduct so that they themselves contribute, not necessarily consciously, to a government’s model of social order’ (1997: 6). This makes them easy targets for normative critique (Calligaro, 2013), but it also turns them into a challenge for disciplines like archaeology, where Eurocentrism and the effects of EUrope has been discussed since the 1990s (Babić et al., 2017; English, 2008; Gramsch, 2000, 2013; Graves-Brown et al., 1996; Gröhn, 2004; Högberg, 2006; Hølleland, 2008a; Kristiansen 2008; Peckham, 2003; Pluciennik, 1998; Tzanidaki, 2000; Willems, 1999). In this discussion most voices agree that European archaeology needs to be globally minded and politically aware, and that ‘using archaeology to try to build an emotive commitment to European identity is a bad idea’ (Babić et al., 2017: 6).…”
Section: Heritage: the New Soul Of Europe?mentioning
confidence: 99%
“…The response to the question of whether the EU’s homogenising rhetoric survived the implementation of the Culture programs is therefore yes, at least in the places where politicians and publics met archaeology. In a recent discussion article, Tim Murray suggested that the greatest gift of European archaeology to the project of world archaeology would be to ‘protect society from archaeology’ by exposing the assumptions that have enabled ethnic essentialism (Babić et al., 2017: 22). While there are surely other benefits to the involvement of European archaeology in settings like the EU cultural funding programs, this critical potential could have been explored further.…”
Section: Commonality Through Peoplementioning
confidence: 99%